Sailing the ocean of faces: unravelling individual differences in face recognition abilities - Leong, Bryan Qi Zheng (2024)
Even though it has generally been assumed that humans are experts in face recognition, the ability to learn and recognize faces varies considerably across individuals. However, it is still unclear to what extent the use of facial information and/or underlying processes differs across individuals. This dissertation consists of four empirical chapters that aimed to explore the role of low-level visual processing to higher-level processes in face recognition ability (FRA) at an individual level. In the first empirical chapter (Chapter 2), we examined how the use of different bands of spatial frequency (SF) information influences FRA at different stages of face recognition. While studies have found that low SF information is important for accurate face recognition, whether it facilitates individual differences in FRA remains unexplored. In our study, we found that low and high SF information are equally important and informative in face learning and face recognition. However, no significant association was found between the recognition performance of low and high SF-filtered faces with FRA, this argues that SF processing does not contribute to individual differences in face recognition.